2021
DOI: 10.1159/000518545
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Assessment: Clinical Effectiveness and Safety of Extended-Release Calcifediol

Abstract: <b><i>Introduction:</i></b> The safety and efficacy of extended-release calcifediol (ERC) as a treatment for secondary hyperparathyroidism (SHPT) in adults with stage 3 or 4 chronic kidney disease (CKD) and vitamin D insufficiency (VDI) has been demonstrated in prospective randomized clinical trials (RCTs). ERC (Rayaldee<sup>®</sup>) was approved by the Food and Drug Administration in 2016 on the basis of these prospective RCTs. The current retrospective study assessed the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
4
0
3
Order By: Relevance
“…The gradual elevation of 25-hydroxyvitamin D with ERC to levels as high as 92.5 ng/mL over a 26-week period had no adverse effects on safety parameters [ 42 , 68 ]. These trial data are supported by emerging real-world data by Fadda et al (2021) [ 69 ]. This study confirmed ERC’s effectiveness in increasing serum 25-hydroxyvitamin D and reducing PTH levels without a statistically significant or notable impact on serum calcium and phosphate levels (on average, calcium went from 9.2 ± 0.1 mg/dL to 9.3 ± 0.1 mg/dL and phosphate went from 3.8 ± 0.1 mg/dL to 3.9 ± 0.1 mg/dL).…”
Section: Extended-release Calcifediol: a Combination Of Efficacy And ...supporting
confidence: 64%
See 1 more Smart Citation
“…The gradual elevation of 25-hydroxyvitamin D with ERC to levels as high as 92.5 ng/mL over a 26-week period had no adverse effects on safety parameters [ 42 , 68 ]. These trial data are supported by emerging real-world data by Fadda et al (2021) [ 69 ]. This study confirmed ERC’s effectiveness in increasing serum 25-hydroxyvitamin D and reducing PTH levels without a statistically significant or notable impact on serum calcium and phosphate levels (on average, calcium went from 9.2 ± 0.1 mg/dL to 9.3 ± 0.1 mg/dL and phosphate went from 3.8 ± 0.1 mg/dL to 3.9 ± 0.1 mg/dL).…”
Section: Extended-release Calcifediol: a Combination Of Efficacy And ...supporting
confidence: 64%
“…VDR—vitamin D receptor, 24,25(OH)2D—24,25-dihydroxyvitamin D (inactive prohormone), 1,24,25(OH)3D—1,24,25 trihydroxyvitamin D (inactive hormone), Ca—calcium, P—phosphorus, FGF23—Fibroblast growth factor-23, PTH—parathyroid hormone, CYP27A1—25-hydroxylase, CYP27B1—1α-hydroxylase, CYP24A1—24-hydroxylase. Adapted from Cozzolino et al [ 41 ], Christensen et al [ 10 ], extended with data from Sprague et al [ 42 , 68 ] and Fadda et al [ 69 ].…”
Section: Figurementioning
confidence: 99%
“…These clinical trials have established the efficacy of ERC for increasing serum 25D levels and reducing PTH with minimal changes in serum Ca or P levels in adult patients with stage 3-4 CKD and VDI. Corresponding real-world clinical data have confirmed the data obtained from RCTs [24] but real-world comparative data are lacking. The lack of such comparative data led to the current evaluation of real-world clinical experience with the available treatment options to raise serum 25D and reduce elevated PTH during a 12-month period.…”
Section: Introductionmentioning
confidence: 83%
“…Data from two real-world clinical studies (Studies 1 and 2) and two prospective RCTs (Studies 3 and 4) in CKD patients were analyzed to assess the influence of BW on the relative capabilities of vitamin D supplements and ERC to adequately raise 25OHD for effective management of SHPT. Real-world data were obtained from nondialysis patients with stage 3–5 CKD undergoing standard-of-care treatment at European facilities operated by Fresenius Medical Care (FMC) (Study 1) and from patients with stage 3–4 CKD, SHPT, and VDI from multiple USA clinics (Study 2; WIRB 1252915) [ 33 ]. Prospective data were obtained from two US RCTs conducted in patients with stage 3–4 CKD, SHPT, and VDI which examined short-term increases in serum 25OHD during ERC or cholecalciferol treatment (Study 3; NCT03588884; Advarra PRO00025210) or longer term increases in 25OHD with ERC as a function of BW (Study 4; NCT01651000, NCT01704079; Advarra PRO00007820) [ 34 ].…”
Section: Methodsmentioning
confidence: 99%